The Current Status of Antisense Gene Therapies for Bacteria-caused Diseases Challenges and Opportunities - Li, Jiawei; Liang, Xuejun; Wang, Fangxin; Wang, Juping; Ding, Feng (Current Pharmaceutical Design, 2023)
Bacteria-caused diseases continue to pose a serious threat to human health. The current situation of overused antibiotics against those diseases further spurs and exacerbates the ever-increasing drug resistance problems, which really leaves us very few options to combat those nasty bugs. Gene therapies based on the antisense oligonucleotide, though developed more than 40 years ago, did not reform the current treatments as originally expected. Along with the advances of new delivery technologies, this old field thrives again. In addition, newly evolving gene-editing tools based on the CRISPR-Cas system shed new light on this old field, bringing a breeze of hope to gene therapies for bacteria-caused diseases. As a fast-growing field, we strive to summarize in this review the recent progress in using gene therapies in those areas, analyze the potential challenges or problems from using antisense or gene-editing tools for targeting bacterial diseases and seek to explore any potential solutions to the current dilemmas. As a short review, we will focus our discussion mainly on antisense oligonucleotide-based gene therapies while briefly touching on the CRISPR-Cas based ones as the latter is just beginning to get more attention for application in the prokaryotic kingdom.
Keywords: gene therapy